1995
DOI: 10.1143/jjap.34.302
|View full text |Cite
|
Sign up to set email alerts
|

H2Partial Pressure Dependences of CH3Radical Density and Effects of H2Dilution on Carbon Thin-Film Formation in RF Discharge CH4Plasma

Abstract: Both the CH3 radical density and carbon thin-film formation were investigated in an RF-discharge CH4/H2 plasma. In this plasma, although CH3 radical density was almost constant, the deposition rate decreased markedly with increasing H2 partial pressure. These results suggested that the surface loss of the radicals was decreased due to the change in surface composition of the film, and also the film etching was enhanced with increasing H2 partial pressure. Therefore, the deposition rate of the carbon thin film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Recently, a study has reported on the fundamental bands of the 10 B and 11 B isotopomers of BO in their ground 2 + states, detected in natural abundance in the O + BCl 3 reaction, at Doppler limited resolution using tuneable diode laser absorption spectroscopy. It extended a preliminary study reported earlier, in which only the spectrum of 11 BO was examined quantitatively [120]. The radicals were made in a 1 m long White-type absorption cell with 26 passes, following the method described by Clyne et al and Llewellyn et al [121,122].…”
Section: Molecular Spectroscopy Of the Bo Radicalmentioning
confidence: 74%
See 2 more Smart Citations
“…Recently, a study has reported on the fundamental bands of the 10 B and 11 B isotopomers of BO in their ground 2 + states, detected in natural abundance in the O + BCl 3 reaction, at Doppler limited resolution using tuneable diode laser absorption spectroscopy. It extended a preliminary study reported earlier, in which only the spectrum of 11 BO was examined quantitatively [120]. The radicals were made in a 1 m long White-type absorption cell with 26 passes, following the method described by Clyne et al and Llewellyn et al [121,122].…”
Section: Molecular Spectroscopy Of the Bo Radicalmentioning
confidence: 74%
“…investigating the influence of rare gases on the plasma. They have also combined IR absorption with emission spectroscopy and investigated the effect of water vapour on the methyl radical concentration in argon/methane and argon/methanol RF plasmas using TDLAS [17,18,[41][42][43]. Kim…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunable diode laser absorption spectroscopy (TDLAS) in the mid-infrared spectral region between 3 and 20 µm is a non-invasive technique for measuring number densities of stable molecules and radicals. TDLAS can also be used to determine neutral gas temperatures [1] and to investigate dissociation processes [2][3][4][5]. Due to their small laser line width (about 10 −4 cm −1 ) the lead-salt diode lasers used in the mid-infrared region are well suited for high resolution spectroscopy purposes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…TDLAS is increasingly being used in the spectral region between 3 and 20 µm for measuring the concentrations of free radicals, transient molecules and stable products in their electronic ground states. TDLAS can also be used to measure neutral gas temperatures [2] and to investigate dissociation processes of molecular low temperature plasmas [3][4][5][6]. The main applications of TDLAS until now have been for investigating molecules and radicals in fluorocarbon etching plasmas [2,5,7], in plasmas containing hydrocarbons [6, 8-14, 60,63] and nitrogen, hydrogen and oxygen [58,59,61,62].…”
Section: Introductionmentioning
confidence: 99%